Wilayah Al-Faqīh dalam Politik Shī’ah - Fathullah (Asy-Syari’ah : Jurnal Hukum Islam, 2019)
Historically the system of government of Shī‘ah refers to the imāmāh system, which is a political doctrine which states that the Islamic government after the death of the Prophet Muhammad was the absolute right of the ahl al-bait (family of the Prophet), namely Ali bin Abi Talib and eleven descendants. This is considered by many observers as not providing an opportunity for other parties to obtain the same rights, namely the right to be elected as the leader of the state. In Shī’ism, the term concept of the region of al-Faqīh (power of the faqīh), or an Islamic jurist, is known. With this new system, Shī‘ah Islam has begun a new chapter in a fairly democratic system of government. A system of government that practices the law of God, which is supervised by the experts of religious jurisprudence (faqīh), as in the practice of the al-Faqīh Region system, will outperform all systems of government that are unfair in this world. Because with a system of government like this, Muslims will avoid mistakes in carrying out the wheels of government. Keywords: shi’ah, imamiyah, wilayah al-Faqih